Vojta Therapy in Medical Rehabilitation of Children with Consequences of Perinatal Central Nervous System Affections - Natalya A. Mikitchenko; Maria G. Degtyareva; Irina I. Ivanova; Olga U. Smotrina; Zareta Kh. Shungarova; Elena V. Gusakova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
INTRODUCTION. According to the Federal Statistical Observation of the Ministry of Health of the Russian Federation, perinatal CentralNervous System affections are one of the leading causes of childhood disability. The development and scientific substantiation of newnon-drug technologies for medical rehabilitation of children with perinatal lesions of the Central Nervous System remains the maintask. A promising technique is Vojta-therapy, a method based on the activation of motor reflexes due to irritation of certain areas onthe child's body.AIM. Scientific substantiation of the use of Vojta therapy in the medical rehabilitation of children with the consequences of perinatalCentral Nervous System affections.MATERIAL AND METHODS. Clinical observations were performed in 110 children with perinatal Central Nervous System affectionsbetween the ages of 2 and 12 months. The comparison groups were formed depending on the nature of kinesiotherapy: the studygroup (n=55) - children who received Vojta therapy; the comparison group (n=55) - children who did not receive Vojta-therapy. Weused clinical and neurological examination, INFANIB score, and SPSS 23.0 statistical analysis.RESULTS AND DISCUSSION Analysis of the clinical and neurological examination data after Vojta therapy revealed a statisticallysignificant increase in the overall motor activity of children. When the method was included in the rehabilitation of patients under theage of 4 months, the number of children with delayed reflex extinction decreased, at the age of 4-8 months, the appearance of coupsand crawling was recorded, at the age of 8 months, the walking skill was formed in a timely manner. By the adjusted age of 1 year,patients receiving Vojta therapy were diagnosed with cerebral palsy 2 times less often than in the comparison group.CONCLUSION. The inclusion of Vojta therapy in the program of medical rehabilitation of children with the consequences of perinatalCentral Nervous System affections contributed to the reduction of pathological motor activity, improvement of muscle tone andthe formation of age-related skills. The use of Vojta therapy in children with the consequences of perinatal Central Nervous Systemaffections up to 8 months determined a more pronounced increase in the grade score on the INFANIB scale and helped to reduce thefrequency of cerebral palsy formation by 2 times.